2019
DOI: 10.21511/ppm.17(2).2019.13
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the efficiency of higher education: case of Bosnia and Herzegovina

Abstract: This paper is devoted to measuring the efficiency of the higher education of Bosnia and Herzegovina. The data envelopment analysis method was applied, considering the number of enrolled students, budget financing, co-financing, self-financing as inputs, and the number of graduated students according to the field of education as the output. Measuring the relative efficiency of main fields of the higher education system of Bosnia and Herzegovina, the authors found that the agriculture is the most efficient field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In the case of Bosnia and Herzegovina, this is a common practice in its higher learning institutions. Nowadays, the country's higher educational quality assurance is on track to closely aligning itself with European Union standards and norms (Brankovic & Brankovic, 2013;Constantinides & Stagno, 2011;Figurek, Goncharuk, Shynkarenko, & Kovalenko, 2019). This paper showcases Bosnia and Herzegovina's educational quality assurance by utilizing textual analysis methods similar to those employed by Ilinska et al (2016), Cunningham-Nelson et al (2018, and Zhang and Law (2013).…”
Section: Literature Reviewmentioning
confidence: 98%
“…In the case of Bosnia and Herzegovina, this is a common practice in its higher learning institutions. Nowadays, the country's higher educational quality assurance is on track to closely aligning itself with European Union standards and norms (Brankovic & Brankovic, 2013;Constantinides & Stagno, 2011;Figurek, Goncharuk, Shynkarenko, & Kovalenko, 2019). This paper showcases Bosnia and Herzegovina's educational quality assurance by utilizing textual analysis methods similar to those employed by Ilinska et al (2016), Cunningham-Nelson et al (2018, and Zhang and Law (2013).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Technical efficiency incorporates the value added in educational institutions as an output of the educational system (López-Matín & Gaviria, 2016). Therefore, technical efficiency, like many other studies (Figurek et al, 2019;Mahmudi et al, 2014;Nazarko & Saparauskas, 2014), is used in this study as a measure of efficiency of higher educational institutions in Bangladesh and comparing efficiency among them with an estimated efficiency score.…”
Section: Conceptual Framework Of Efficiency Measurementmentioning
confidence: 99%
“…The results showed that agriculture is the most efficient domain while manufacturing technologies, construction, and engineering had the worst performance in terms of budget expenditures. They concluded by emphasizing the need to find proper solutions for reducing the number of graduate students in the fields of mathematics and natural sciences, engineering, manufacturing technologies, and construction [13].…”
Section: Literature Survey Of Dea Application In Higher Education Ins...mentioning
confidence: 99%